Advances in flavours and fragrances from the sensation to the synthesis - Swift, Karl A. D. (Royal Society of Chemistry, 2002)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. The chemistry of flavours and fragrances is of great interest to academics and industrialists alike. Bringing together international contributors, this book presents the most recent research in this key area. Diverse topics such as structure-activity relationships; analytical techniques; natural products and essential oils; and organic and bioorganic chemistry are discussed, along with flavours and foods. Advances in Flavours and Fragrances: From the Sensation to the Synthesis will be a welcome addition to the bookshelves of all practitioners with a common interest in this fascinating area.
Contains 16 of the twenty papers presented at Flavours and Fragrances 2001 : From the Sensation to the Synthesis, held on 16-18 May 2001 at the University of Warwick, Coventry, England.
Keywords: Flavoring essences -- Congresses.; Food -- Odor -- Congresses.; elektronické knihy; electronic books